Pengaruh Berpikir Induktif Dalam Pembelajaran Getaran dan Gelombang Dikelas VIII SMPN Bosar Galugur Kecamatan Tanah Jawa - Surbakti, Mariana; Nainggolan, Irawati Kristin M.; Sitorus, Parlindungan (Jurnal Visi Eksakta, 2022)
This research aims to find out the influence of inductive thinking learning models in physics learning on Vibration and Wave Material of Grade VIII in SMPN Bosar Galugur Village, Tanah Jawa Sub-District. This type of research is a "true" experimental research with a research population that is all grade VIII junior high students in Bosar Galugur Village, Tanah Jawa Sub-District. With the Cluster Random Sampling technique, it is considered a research sample of experimental classes (13 students) and control classes (12 students). The instruments used are student results tests with multiple selection forms that have been performed through validation tests as well as student activity observation sheets. The results of the data analysis were an average score of 61.92 experiment class post-test with a standard deviation of 10.11 and an average post-test control class score of 41.66 with a standard deviation of 12.49. The hypothesis of this study was tested with a one-party t test for experiment class post test data and control classes for α=0.05 and dk=23 obtained thitung =4.48 and ttabel =1.71, with thitung>ttabel then Ha accepted and H0 rejected. Thus it can be concluded based on the above calculation results that there is a significant influence of inductive thinking learning model in physics learning on Vibration and Wave Material Grade VIII in Bosar Galugur Village of Tanah Jawa Sub-district.